Membangun Keadilan dari Memori: Pelajaran Moral dan Sosial dari Adegan Ketidakadilan dalam Film Bumi Manusia - Abraham, Agustinus (Lembag, 2025)
This study examines the representation of injustice in the film Bumi Manusia as a medium of collective memory and moral reflection for contemporary Indonesian society. Using a qualitative method with a literature-based approach, the research identifies seven key scenes that portray forms of structural injustice related to race, gender, law, power, and access to knowledge. The analysis reveals that these depictions not only illustrate the oppressive colonial system but also resonate with present-day social realities in Indonesia, where legal inequality, marginalization, and power abuse persist. The findings show that the film offers significant moral and social lessons: the primacy of human dignity, the necessity of a humane legal system, the role of education as a path to liberation, and the ethical responsibilities embedded in power relations. Furthermore, the film’s narrative demonstrates how historical memory shapes critical awareness and encourages resistance against ongoing injustice. The study concludes that Bumi Manusia functions as a cultural text that bridges past and present, providing insights for building a just, dignified, and civilized society today.